360-OR: Hyperglucagonemia Reduces De Novo Lipogenesis and Increases Gluconeogenesis in Healthy Subjects - CHEN, XI; CARLI, FABRIZIA; PEZZICA, SAMANTHA; MOCCIARO, GABRIELE; CIOCIARO, DEMETRIO; GASTALDELLI, AMALIA; DEFRONZO, RALPH A.; TRIPATHY, DEVJIT (Diabetes (New York, N.Y.), 2022)
Although the effect of glucagon on glucose metabolism has been well characterized, its effect on lipid metabolism, particularly lipolysis and de novo lipogenesis, in humans in vivo has been poorly studied with controversial results. We examined the effect of short-term hyperglucagonemia on de novo lipogenesis (DNL) and endogenous glucose production (EGP) in 8 healthy normal glucose tolerant subjects (5M/3F, age=35±5, BMI= 24±1) who received a 12-hour (6PM to 6AM) glucagon infusion (6ng/kg/min) infusion with measurement of EGP (3-3H-glucose) on the following morning 6-AM. Subjects received deuterated water (D2O, 5g/kg fat free mass) at PM on the night prior to study. 8 weeks later subjects returned for a repeat study with 12-hour infusion of normal saline. DNL was quantified by measuring the incorporation of deuterated water into circulating triglycerides. Gluconeogenic rate was measured as (EGP) x (plasma C5/C2 glucose ratio) (EGP) x (plasma C5/C2 glucose ratio) . Plasma esterified and non-esterified FFA levels were measured with gas chromatography mass spectrometry (GC-MS) . Plasma glucagon increased from 57±3 to 219±21 pg/ml within one hour and remained elevated throughout the study. DNL was significantly decreased (1.64 ± 0.58% vs. 3.± 0.98%, p<0.05) after glucagon versus saline infusion. Both plasma palmitate (0.73 ± 0.vs. 0.67 ± 0.mmol/L) and total FFA (1.35 ± 0.vs. 1.21 ±0.mmol/L) concentrations were elevated after glucagon infusion (p<0.05) . EGP increased following glucagon infusion (2.13 ± 0.14 vs. 1.97± 0.11mg/kg/min, p =0.006) . The increase in EGP was primarily due to increased gluconeogenesis (1.48 ± 0.14 vs. 1.27 ± 0.11, p=0.02) , while the rate of glycogenolysis did not change (0.65± 0.14 vs. 0.70± 0.11, p=ns) . Conclusion: Short-term (12-hour) physiologic hyperglucagonemia in healthy subjects reduces hepatic de novo lipogenesis, stimulates adipose tissue lipolysis, and increases hepatic glucose production by increasing gluconeogenesis.